6- An Issue Overlooked in Nigeria’s Reforms: The Continuation of Government Discriminatory Practices - Isumonah, V. Adefemi (African Sociological Review, 2006)
On the basis of the view that the democratic structures established by the 1999 General Elections are adequate for administering Nigeria, the Obasanjo Administration has refused to convene a National Conference of popularly elected delegates to design a new Constitution for Nigeria. It has for this reason devoted itself to economic reforms, initiating political reforms pretentiously or actually in pursuit of its interest in political control. According to informed opinion, there are many neglected steps even in the Administration’s economic reforms project. But this paper is concerned with an aspect of political reform which in the Administration’s stillborn political reform initiatives did not receive the urgent attention it deserves for its high political and economic impact on the majority of Nigerians. This is the dichotomy governments at all levels of the Nigerian federation – federal, state and local – make between ‘indigenes’ and ‘non-indigenes’ in the allocation of economic and social benefits. It shows the impact of this dichotomy on the rights to seek elective office and demand political accountability, which neither economic reform nor political reform initiatives have accorded necessary attention.